FORECASTING THE MAIN STRUCTURAL CHANGES IN AGRICULTURE OF THE REPUBLIC OF SERBIA - Stanojević, Jelena; Radivojević, Vladimir; Stanišić, Tanja (Economics of Agriculture, 2021)
Structural changes in agriculture, rural areas and regions, as well as in economic activities related to the production and trade of agricultural products, most often occur as a response to periodic changes in general economic and social conditions. In order to formulate effective policies and strategies, policy makers need adequate information about the main structural changes in agriculture. Therefore, based on the information framework of the Statistical Office of the Republic of Serbia, the article primarily focuses on changes of agricultural output in Serbia, respectively changes in crop and animal production, and agricultural services. The research aims to analyze changes in the structure of agricultural output in the period from 2007 to 2019 in order to identify its future trend by applying the forecast function. The research results show that the agricultural production of goods and services will keep the positive trend with a dominant share of crop production.